Deconstruction the Theatrical Time in the Expressionist Doctrine (Al-Academy, 2018)
Time affects all elements of the intellectual scene or the theatrical scene. It came along with the theatrical doctrines according to the conditions of those doctrines and their conceptual ideas or the method of their mechanisms in the application. While it is classically or realistically integrated, we see it in the expressionist doctrine inconsistent and its inconsistency makes it responsive for the deconstruction strategy. Hence the researcher entitled his study (deconstruction the theatrical time in the expressionist doctrine) so that deconstruction would be a field for his study. The study starts with an introduction presenting the research problem, importance and objective. The theoretical framework consisted of three sections. The first section (time deconstruction strategy), the second section (time in the expressionist doctrine) and the third section (time deconstruction in the expressionist doctrine). The research procedures include an intentional sample represented by the play show (playing and worry). A number of results reached at are as follows: the insufficiency of any time significance will give the audience constant presence and will give the readers diversity and spread. The most important conclusion was that recalling the time of the multiple reading results in recalling of the subconscious time